2013
DOI: 10.1103/physreva.87.032102
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of parameter-estimation precision in noisy systems by dynamical decoupling pulses

Abstract: We present a scheme to enhance precision of parameter estimation (PPE) in noise systems via employing dynamical decoupling pulses. The exact analytical expression for the estimation precision of unknown parameter is obtained by using the transfer matrix and time-dependent Kraus operators. We show that PPE in noise systems can be preserved in the Heisenberg limit by controlling of dynamical decoupling pulses. It is found that larger number of pulses and longer reservoir correlation time can remarkably protect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…This is similar to what is done in optimal control theory or bangbang control [31,32], with the requirement that the desired evolution H S is not completely eliminated. For the simple case of orthogonal s x y , noise, fast intermediate s z operations suffice (see [28]). The applicability of dynamical decoupling techniques is determined by the timescales of the problem.…”
Section: Decoupling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to what is done in optimal control theory or bangbang control [31,32], with the requirement that the desired evolution H S is not completely eliminated. For the simple case of orthogonal s x y , noise, fast intermediate s z operations suffice (see [28]). The applicability of dynamical decoupling techniques is determined by the timescales of the problem.…”
Section: Decoupling Strategymentioning
confidence: 99%
“…Identifying schemes that realize this advantage in practice are of high theoretical and practical relevance. It was shown that quantum error correction [23][24][25][26], dynamical decoupling [27,28] or limited control over the environment [29,30] allow for an improved scaling for certain, specific noise processes.…”
Section: Introductionmentioning
confidence: 99%
“…And the use of entangled states has been proved to * luxiaoming@gmail.com † xgwang1208@zju.edu.cn only give a constant improvement for the ultimate precision, but still follows the SQL [14][15][16]. Several strategies and techniques have been proposed and used to protect the precision of atomic clocks from noises [17][18][19][20][21]. Whereas, the evaluation and optimization of generic multiqubit MWI schemes for quantum sensing under decoherence still remain challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, utilizing the quantum character, such as the quantum squeezing [18], quantum entanglement [19], NOON state [20], entangled coherent states [21] and so on, the precision of quantum parameter estimation can be enhanced and surpass the standard quantum limit, even arrive the Heisenberg limit 1/N . Other quantum technology, such as weak measurement [22,23], dynamical decoupling [24], quantum error correction [25], can also be used to enhance the precision of quantum metrology. The multiple quantum parameters estimation have also been reported [26,27].…”
Section: Introductionmentioning
confidence: 99%